The Composition and Cyclical Behavior of Trade Flows in Emerging Economies - De Bock, Reinout (IMF Working Papers; Working Paper ;, 2010)
Trade flows data show that the composition and cyclical properties of imports are similar in developed economies and emerging markets (EM) but this is not the case for exports. Unlike developed economies, (i) EM export few or only a selective set of capital goods and (ii) capital good and overall exports tend to be acyclical. The lack of procyclicality in exports drives the strong countercyclicality of EM trade balances observed in previous studies. A quantitative exercise demonstrates how the standard small open economy business cycle model can be improved for EM by incorporating these features.